Implementasi Model Pembelajaran Numbered Head Together dalam Meningkatkan Keaktifan Belajar Siswa pada Mata Pelajaran PAI di Kelas X SMA Negeri 1 Teluk Mengkudu - Wardahtul Nazla; Yurmaini Yurmaini; Fitri Yulia (HIBRUL ULAMA, 2025)
This study aims to describe the implementation of the Numbered Heads Together (NHT) cooperative learning model to improve student engagement in Islamic Education (PAI) for Grade X at SMA Negeri 1 Teluk Mengkudu. The research uses a qualitative case study approach. Data were collected through non-participant observation, semi-structured interviews, and documentation from the PAI teacher, Grade X students, and the vice principal for curriculum affairs. The collected data were analyzed using Miles and Huberman's interactive model. The findings show that the implementation of the NHT model, through heterogeneous group formation, numbering, group discussions, and random number calling, increased students’ involvement in discussions, asking questions, and expressing opinions, while also strengthening individual responsibility within the groups. However, the implementation faced challenges such as limited time, dominance by certain students during discussions, and some students’ anxiety or lack of self-confidence. In conclusion, NHT proved effective in enhancing student engagement in Islamic Education, though class and time management need to be improved to ensure more equitable participation.